STRUKTUR PENYAJIAN TARI JEPIN PIRING DI KERATON PAKUNEGARA KESUMA KECAMATAN TAYAN KABUPATEN SANGGAU - Cendi, Indah Putri; Ismunandar, Ismunandar; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the basic and supporting elements found in Jepin Piring dance and can be preserved and re-studied by the next generation. The research method used is the description method. The data of this study are the main elements and supporting elements of Jepin Piring dance, as well as the contribution of Jepin Piring dance to the learning of arts and culture in the 8th grade. The data sources include Gusti Balya, Gusti Yusri S.H and Sriwati who know the structure of Jepin Piring dance presentation.The results of this study describe the main elements and supporting elements. Motion has 3 different types of motion, divided into initial motion, core motion and closing motion. The floor design used is a vertical line pattern. The dramatic design of multiple cones, with the movement of dancers adjusting the tempo of musical accompaniment and group composition using a concurrent design. Music accompaniment uses Malay musical instruments and poetry. Cosmetology and clothing are Malay clothing and natural makeup. The venue used can be either a closed or open arena. Keywords :Presentation Structure, Jepin Piring Traditional Dance.